La educación financiera y las finanzas familiares en los comerciantes del mercado Señor de los Milagros de Contamana año 2022 - Pezo Shapiama, Carlos Daniel (2022)
The general objective of the research was to determine the relationship between financial education and family finances in the merchants of the Mercado Señor de los Milagros de Contamana AÑO 2022, in which an applied type study, correlational level and non-experimental design was chosen, where 400 merchants were taken as a population, to whom the survey technique was applied and the question questionnaire as an instrument. Among the results, it was possible to determine that financial education in merchants is qualified as regular (27%), because they sometimes have knowledge of how to carry out financial risk controls, and make a family budget to plan the distribution of their income, they also sometimes assess your ability to pay before applying for a loan. On the other hand, personal finances are regular (26%), since they sometimes make a financial plan for their family's expenses and income, but they never have medium-term goals to save, as they almost never support themselves for the payment of their debts in relatives who lend them without interest, however, sometimes they supervise their unattained goals and thus be able to know what they are failing in. In conclusion, it was determined that there is a considerable positive relationship between financial education and family finances in merchants, which was confirmed by a correlation coefficient of 0.770.